2015
DOI: 10.1148/radiol.15142394
|View full text |Cite
|
Sign up to set email alerts
|

Single Hepatocellular Carcinoma: Preoperative MR Imaging to Predict Early Recurrence after Curative Resection

Abstract: Purpose:To identify magnetic resonance (MR) imaging features that enable prediction of early recurrence (,2 years) after curative resection of hepatocellular carcinoma (HCC) and to derive a preoperative prediction model. Materials and Methods:This retrospective study was approved by the institutional review board. The requirement to obtain written informed consent was waived. A total of 268 patients who underwent hepatic resection for a single HCC from January 2008 to August 2011 were divided into two cohorts:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
139
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 185 publications
(155 citation statements)
references
References 45 publications
14
139
2
Order By: Relevance
“…This proportion is similar to that in our recent study in which 4.9% of 225 HCCs showed IRE and were thus categorized as LR-M [5], but lower than that in our earlier study in which 11.8% of the 187 HCCs showed IRE [3]. A likely reason for this discrepancy is our strict criteria for evaluation of IRE in the current study; we considered IRE to be positive only when both of the two reviewers agreed on its presence.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This proportion is similar to that in our recent study in which 4.9% of 225 HCCs showed IRE and were thus categorized as LR-M [5], but lower than that in our earlier study in which 11.8% of the 187 HCCs showed IRE [3]. A likely reason for this discrepancy is our strict criteria for evaluation of IRE in the current study; we considered IRE to be positive only when both of the two reviewers agreed on its presence.…”
Section: Discussionsupporting
confidence: 85%
“…This study aimed to seek a histopathologic explanation for the results of our previous HCC studies in which IRE was an independent imaging feature associated with poor prognosis after curative resection [3,5]. We found that the histopathologic features of IRE-HCCs included sinusoid-like microvascular pattern, macrotrabecular pattern, a high proportion of tumor necrosis and fibrous stroma, and expression of stemness markers, which have been reported as characteristics of aggressive and poor prognostic HCCs [20,21,23,25,43].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations